Portugal sobre a literacia em saúde: resultados de um think tank nacional - Oliveira, Hernâni Zão (2020)
Following a participatory action research study, Portugal witnessed, in 2019, the development of a national Think Tank with the presence of entities, professionals and members of civil society, to discuss collaborative strategies to increase Health Literacy of the population. The results of this study point to the need of increasing the perception of the value of Health Literacy for the whole of society, and recognizing the efforts of professionals dedicated to its promotion. Intervening stakeholders also recognize the need for collaborative training in the area of Health Communication and Health Literacy itself.